2016
DOI: 10.1080/15548627.2016.1183844
|View full text |Cite|
|
Sign up to set email alerts
|

Cocaine induces astrocytosis through ER stress-mediated activation of autophagy

Abstract: Cocaine is known to induce inflammation, thereby contributing in part, to the pathogenesis of neurodegeneration. A recent study from our lab has revealed a link between macroautophagy/autophagy and microglial activation. The current study was aimed at investigating whether cocaine could also mediate activation of astrocytes and, whether this process involved induction of autophagy. Our findings demonstrated that cocaine mediated the activation of astrocytes by altering the levels of autophagy markers, such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
78
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(85 citation statements)
references
References 56 publications
(67 reference statements)
7
78
0
Order By: Relevance
“…This study demonstrated that although SREBP2 activation and HMGCR levels were increased, HMGCR activity was reduced by 70% under ER stress, which led to decreased cholesterol synthesis. There are a number of reports of ER stress induced by cocaine or Tat contributing to neurotoxicity (Desai et al 2010; Fan and He 2016; Ma et al 2016; Periyasamy et al 2016). Therefore, it is possible that ER stress may be an upstream event mediating cholesterol dysregulation following cocaine and Tat exposure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study demonstrated that although SREBP2 activation and HMGCR levels were increased, HMGCR activity was reduced by 70% under ER stress, which led to decreased cholesterol synthesis. There are a number of reports of ER stress induced by cocaine or Tat contributing to neurotoxicity (Desai et al 2010; Fan and He 2016; Ma et al 2016; Periyasamy et al 2016). Therefore, it is possible that ER stress may be an upstream event mediating cholesterol dysregulation following cocaine and Tat exposure.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, cocaine use is a major risk factor for becoming infected with HIV and together, HIV and cocaine synergize to increase cellular dysfunction in astrocytes in the brain (Buch et al 2012; Cai et al 2016; Dahal et al 2015; Hauser and Knapp 2014; Reynolds et al 2006; Yang et al 2016). Likewise, HIV infection and cocaine use are associated with myelin loss and synaptodendritic damage (Dash et al 2011; Fitting et al 2013; Kim et al 2003; Periyasamy et al 2016), suggesting that dysregulation in CNS cholesterol metabolism may be involved in the progression of neurocognitive impairment. Several studies report toxic synergy between cocaine and HIV proteins such as Tat on cells of the CNS, including astrocytes (Gandhi et al 2010; Wayman et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…1 μg of total RNA was used for the synthesis of complementary DNA as described previously [37]. The reverse transcribed RNA was analyzed with the 7500 Fast Real-Time PCR System (Applied Biosystems, Grand Island, NY) with the RT 2 SYBR Green Fluor qPCR Mastermix (Qiagen, 330510).…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have also implicated the regulatory role of PERK in ER stress-mediated autophagy [49,46]. Drugs of abuse such as cocaine under various experimental conditions have been shown to mediate ER stress, which in turn, regulates the expression of different genes involved in microglial and astrocyte autophagy [50,37]. Morphine-mediated autophagy has also been reported in various cell types, such as bone marrow-derived macrophages [51], neuroblastoma cell line [52], primary hippocampal neurons [43], and microglia [53].…”
Section: Introductionmentioning
confidence: 99%
“…Autophagy initiation begins with the membrane distention from either the ER or Golgi complex, followed by formation of autophagosome, a cup shaped double-membrane structure which sequesters cellular components. Subsequently, autophagosome fuses with the lysosome to form an autolysosome which is the site for degradation of the sequestered cargo by the action of the lysosomal hydrolytic enzymes (2).…”
mentioning
confidence: 99%